Genetic parameters, association of traits and selection of durum wheat genotypes (Triticum turgidum L. var. durum) advanced lines at Injibara, Northwestern Ethiopia - Birkneh Kuru; Ahadu Menzir; Mulusew Kassa (Agrosystems, Geosciences & Environment)
Abstract Durum wheat production and grain quality in Ethiopia are below the global average, primarily due to the limited availability of high‐yielding and industrial‐quality varieties. Assessing genetic variability is essential for breeding high‐yielding cultivars. This study evaluated 45 advanced durum wheat lines (Triticum turgidum L. var. durum) at the Ethiopian Institute of Agricultural Research, Pawe Agricultural Research Center (Kossober sub‐station) during the 2020/2021 cropping season using an alpha lattice design with two replications. Fourteen quantitative traits were analyzed, including 13 yield‐related traits and one grain quality trait (protein content [PC]). Significant genetic variability was observed among the genotypes, with the highest phenotypic coefficients of variation (PCV) and genotypic coefficients of variation (GCV) recorded for grain yield (GY), number of effective tillers plant−1 (ETN), and harvest index (HI). Additionally, GY, ETN, HI, and number of kernel spike−1(KPS) exhibited high broad‐sense heritability (H2b) and genetic advance as a percentage of the mean (GAM), indicating strong genetic control and potential for selection. In contrast, PC showed moderate heritability and low genetic advance, suggesting limited selection efficiency for grain quality improvement. Additive gene effects predominantly influenced ETN, KPS, GY, and HI, making phenotypic selection effective for these traits. GY exhibited strong positive genotypic and phenotypic correlations with HI, number of spikelet spike−1 (SPS), KPS, grain filling period (GFP), and days to maturity (DSM). However, number of non‐effective tiller plant−1 (NNT) showed the highest negative correlation with GY. Genotypically, KPS and GFP had the strongest positive direct effects on GY, while at the phenotypic level, SPS and HI were the most influential. Conversely, DSM, NNT, and plant height (PH) had negative direct effects on GY at both levels. The observed genetic variability and trait associations provide valuable insights for designing selection and hybridization strategies in durum wheat breeding. Selecting genotypes based on traits with strong positive correlations and direct effects on GY is recommended to enhance yield potential.